KEMAMPUAN BERPIKIR KRITIS DITINJAU DARI KEMAMPUAN AKTIVITAS MENGHAFAL AL-QURAN DENGAN PEMBELAJARAN SSCS (SEARCH, SOLVE, CREATE, AND SHARE) - Miladia Arina Manasikana; Iwan Junaedi (UJMES (Uninus Journal of Mathematics Education and Science), 2021)
This study aims to determine the description of the level of critical thinking ability (TKBK) of students in terms of the level of students' ability to memorize the Koran in the SSCS model learning. This type of research is a combination research (mix method). The research subjects in this study were students of class XI IPA 1 MA Al Asror Semarang, Central Java. The results showed: (1) the implementation of the SSCS learning model was effective in fulfilling the classical mastery of students' mathematical critical thinking skills. (2) students with a high level of ability to memorize the Koran are in TKBK 3 (critical). (3) students with the ability level of memorizing the Qur'an are at TKBK 2 (quite critical) and TKBK 1 (less critical). (4) students with low levels of ability to memorize the Qur'an are at TKBK 1 (less critical) and TKBK 0 (not critical).